A carbonothioate‐based highly selective fluorescent probe with a large Stokes shift for detection of Hg2+. (25th October 2017) - Xu, Jing; Xu, Zhenghe; Wang, Zuokai; Liu, Caiyun; Zhu, Baocun; Wang, Xiuru; Wang, Kun; Wang, Jiangting; Sang, Guoqing
Abstract: Mercury (Hg) is one of the heavy metal pollutants in the environment. Even a very small amount of mercury can cause serious harm to human beings. Herein, we reported a new carbonothioate‐based fluorescent probe for the detection of Hg 2+ without interference from other metal ions. This probe possessed a very large Stokes shift (192 nm), which could improve the detection sensitivity by minimizing the interferences resulted from self‐absorption or auto‐fluorescence. With the addition of Hg 2+ to the probe solution, considerable fluorescence enhancement was observed. Additionally, the Hg 2+ concentration of 0–16 μM and fluorescence intensity showed a good linear relationship (y = 22106× + 53108, R 2 = 0.9955). Finally, the proposed probe was used to detect Hg 2+ in real water samples, and its result was satisfactory. Therefore, our proposed probe would provide a promising method for the determination of Hg 2+ in the environment.